PENYELIDIKAN OLEH KEPOLISIAN SEKTOR TENAYAN RAYA TERHADAP TINDAK PIDANA PEMBUANGAN BAYI DI WILAYAH HUKUM TENAYAN RAYA - Ramadani, Fitri; ', Erdianto; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Baby disposal crimes more often happens. This happens due to peope sometimes failed to prevent himself from doing deviant tendencies because of economic interests, biological demands, status and the pride of himself. Even though this evil doings is a form of perversion of the norms and values of humanity. The Police as law enforcement agencies have to cope with this criminal act to avoid recurrence. But in the process of tackling this problem, there are some obstacles of course. Therefore, the author is interested to do research on the phenomenon in order to know the investigation process, obstacles and efforts by police investigation in Tenayan Raya sector against criminal acts of the baby disposal in jurisdiction of Tenayan Raya. To find the answers to these problems, the research done through interview and literature studies. Based on qualitative data analysis by the method of deductive reasoning obtained the answers that the investigation of baby disposal crimes in jurisdiction of Tenayan Raya is already running as it should, but not optimal. Tenayan Raya sector police’s obstacles in the investigation of criminal disposal of baby include: lack of investigators, community, lack of facilities and infrastructure, lack of information and the difficulty expressing the evidences factors. The efforts by the police in the investigation of baby disposal crimes in the Tenayan Raya’s region of law are: adding personnel, making a good relationship with the community, looking for an alternative use of facilities and infrastructure that less, published a wanted list, and disclosing effort of evidences. The author suggests that Tenayan Raya’s police are investigating quickly and thoroughly, making cooperation with other forces such as the institution for the protection of children in this investigation, and completing facilities and infrastructure that is needed.Keywords: Baby disposal, Investigation, Tenayan Raya